Comparison Analysis of Financial Performance of PT Bank Mega Syariah and PT Bank Panin Syariah (Period 2009-2014) - Mahesa, Gema (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Bank Panin Syariah began its operation in 2010. During one year, the asset of Bank Panin Syariah grew for Rp297 billion, from Rp162 billion – in the previous year – to be Rp459 billion. One of shariah banks which assets are in similar group with Bank Panin Syariah is Bank Mega Syariah. Bank Mega Syariah has been operated since 2004. Its profit experienced fluctuations each year, in contrast with Bank Panin Syariah’s profit which positively grew. This phenomenon needs deeper analysis in order to describe the financial performance of both banks as they achieved good financial performance credit, although their company ages and financial status are different. The research aims at assessing financial performances between PT Bank Mega Syariah and PT Bank Panin Syariah, as well as making comparison through statistic test on financial ratio. This comparative research uses quantitative approach, in which it compares financial performance level of PT Bank Mega Syariah with PT Bank Panin Syariah during the observation period. The types of financial ratio analysis used are Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operational Cost of Revenue Ratio (OCR) and Return On Asset (ROA). For making comparison through statistic test, it will use independent sample t-test. The ability of PT Bank Panin Syariah to fulfill its long-term obligation is better than PT Bank Mega Syariah, thus it belongs to the category of ‘quite solvable’. PT Bank Panin Syariah better to collects smooth credit or to solving stuck credit than PT Bank Mega Syariah. But the ability of PT Bank Mega Syariah to produce the profit from the assets used by the bank is better than PT Bank Panin Syariah. PT Bank Mega Syariah’s ability to generate revenue is better than PT Bank Panin Syariah. And the ability of PT Bank Mega Syariah to solve the loan obligations and pay all the deposit are better than PT Bank Panin Syariah. Through independent sample t-test, it can be concluded that the significant difference between financial performances of PT Bank Mega Syariah and PT Bank Panin Syariah is only on its Non Performing Financing (NPF). Keywords: Financial Performance, CAR, NPF, FDR, OCR, ROA, independence sample t-test